(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2021)
Within the framework of Theory of Didactical Situations in Mathematics, we have designed, implemented and assessed two situations for a four year old classroom. These situations were ‘Train Game’ and ‘Invitations and Envelopes Game’. In both cases, counting and the use of natural numbers as ordinals or cardinals is the ideal strategy in order to solve the situation. These are the contents which we want the students to work in a functional and meaningful way due to these characteristics don’t exist in the proposals of textbooks publishers which prevail in most classrooms.